The Synergistic Classroom Interdisciplinary Teaching in the Small College Setting - Angello, Aaron; Campion, Corey (Rutgers University Press, 2020)
"Among the many challenges confronting the liberal arts today is a fundamental disconnect between the curricula that many institutions offer and the training that many students need. Discipline-specific models of teaching and learning can underprepare students for the kinds of interdisciplinary collaboration that employers now expect. Although aware of these expectations and the need for change, many small colleges and universities have struggled to translate interdisciplinarity into programs and curricula that better serve today's students. Written by faculty engaged in the design and delivery of interdisciplinary courses, programs, and experiential learning opportunities in the small college setting, The Synergistic Classroom addresses the many ways faculty can leverage their institutions' small size and openness to pedagogical experimentation to overcome the challenges of limited institutional resources and enrollment concerns and better prepare students for life and work in the twenty-first century. Taken together, the contributions in this volume invite reflection on a variety of important issues that attend the work of small college faculty committed to expanding student learning across disciplinary boundaries"-- Provided by publisher.
Keywords: Small colleges -- United States.; Interdisciplinary approach in education -- United States.; Education, Higher -- Curricula -- United States.; Petites universités -- États-Unis.; Interdisciplinarité en éducation -- États-Unis.; Enseignement supérieur -- Programmes d'études -- États-Unis.; EDUCATION / General.; Education, Higher -- Curricula; Interdisciplinary approach in education; Small colleges; United States; Corey Campion, associate professor, history, global studies, director, master, Arts, humanities program, Hood College, Frederick, Maryland, Aaron Angello, Sophie. M. Libman, Education, Teaching Methods, Materials, Humanities, Teacher, Student Mentoring, liberal arts, Learning, Students, interdisciplinary, Collaboration, Synergistic Classroom, small college faculty, 20th Century.